Negative option values are possible: The impact of Treasury bond futures on the cash U.S. Treasury market - Jordan, Bradford D.; Kuipers, David R. (Journal of Financial Economics, 1997)
This paper uses a unique financial instrument in the U.S. Treasury market to study the price behavior of the put option embedded in the November 2009 14 callable U.S. Treasury bond. We find that, beginning in August 1993, the estimated option value was persistently negative on nearly every day for the ensuing eight months. We show that the anomalous pricing behavior arose because the underlying callable bond became the cheapest to deliver issue against U.S. Treasury bond futures contracts. Hence, this paper provides direct evidence that derivative assets can significantly distort pricing in the primary asset market.